2000
DOI: 10.1177/074823370001600201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro percutaneous absorption of nonylphenol and nonylphenol ethoxylates (NPE-4 and NPE-9) through human, porcine and rat skin

Abstract: The purpose of this study was to assess the percutaneous absorption of nonylphenol (NP) and the nonylphenol ethoxylates, NPE-4 and NPE-9, in human, porcine and rat skin. In vitro studies with the NPEs were conducted for 8 h in flowthrough diffusion cells using topical solutions of 0.1, 1.0 and 10% in PEG-400 or 1% in water (NPE-9 only). NP absorption was assessed as a 1% solution in PEG-400. All compounds were 14C ring-labeled and radioactivity in perfusate was monitored over time. Skin deposition was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The tape strips were discarded. Studies have shown that tape stripping removes the stratum corneum layers (data not shown) and removes surface radioactivity of topically applied substances bound to the stratum corneum 20,21 . Full‐thickness 6 mm punch biopsy specimens of skin were taken and placed immediately into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The tape strips were discarded. Studies have shown that tape stripping removes the stratum corneum layers (data not shown) and removes surface radioactivity of topically applied substances bound to the stratum corneum 20,21 . Full‐thickness 6 mm punch biopsy specimens of skin were taken and placed immediately into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Human exposure to p -NP may occur by cutaneous absorption, ingestion of contaminated food or water, and inhalation (Guenther et al 2003; Monteiro-Riviere et al 2000). Several studies have shown that p -NP binds to both estrogen receptor isoforms (ERα, ERβ), competing with the natural estrogen 17β-estradiol (17β-E 2 ) (Kwack et al 2002; Soto et al 1995; White et al 1994), although with less potency (Blom et al 1998; Nagel et al 1997).…”
mentioning
confidence: 99%
“… 33 Human exposure to p -NP may occur by cutaneous absorption, ingestion of contaminated food or water, and inhalation. 34 , 35 Estrogenic activity of p -NP has been known since 1991 33 and reported in a number of in vitro 36 and in vivo studies. 37 Interestingly, studies in rats showed that maternal exposure to p -NP resulted in an increase in uterine calbinding-D 9k (CaBP-9k) mRNA and protein expression in maternal and neonatal uteri, suggesting its potential transfer through the placenta.…”
Section: Environmental Contaminants: a Threat For Human Reproductive mentioning
confidence: 99%